(untitled) (Portuguese Journal of Family Medicine and General Practice, 2012)
Objective: The objectives the EuroEVA study (Influenza vaccine effectiveness in Europe) were to estimate the effectiveness of the seasonal influenza vaccine (VE) in 2010-2011 in the general population and among individuals 65 years of age and older. Study type: An observational study using the case-control and screening methods Local: Continental Portugal Population: The Portuguese population with no contraindications for influenza vaccination Methods: Two study designs were used to estimate Vaccine Effectiveness (VE): the case-control test-negative design and the screening method. In the test-negative design, influenza-like illness cases (ILI) with laboratory confirmation of infection by the influenza virus were compared with the influenza-like illness cases negative for infection by the influenza virus. The influenza VE was estimated as 1 minus the odds ratio of being vaccinated among the cases versus the controls and adjusted for con- founding by logistic regression. In the screening method, the influenza vaccine coverage of the ILI positive cases was compared with coverage estimated in the general population.The influenza VE was estimated using the Orenstein formula and adjusted for confounding by the Farrington method. Results: The results show that the effectiveness of the influenza vaccine in 2010-2011 was 79% (CI95% 43-94) using the test- negative design and 70% (95%CI 32%-87%) using the screening method. After adjusting for confounders, the VE decreased re- spectively to 58% (95%CI -61%-89%) and 64% (95%CI 17%-84%). Conclusions: The estimates of the influenza vaccine effectiveness obtained by the two methods were similar and are within the values published in other studies conducted during the 2010-2011 season. The present study was unable to estimate the VE in the target groups for influenza vaccination. These results strengthen the need for international multicentre studies with a common protocol such as I-MOVE (Monitoring influenza vaccine efectiveness during influenza seasons and pandemics in the European Union).